Synthesis and antioxidant activities of new nickel(II) complexes derived from 4-benzyloxysalicylidene-S-methyl/propyl thiosemicarbazones - EĞLENCE-BAKIR, Songül (Turk J Chem, 2021)
Six nickel(II) complexes of the N(2)O(2) chelating thiosemicarbazones were synthesized using N(1)-4-benzyloxysalicylidene-S-methyl/propyl thiosemicarbazone and methoxy-substitute-salicylaldehydes in the presence of Ni(II) ion by template reaction. The structures of thiosemicarbazones and nickel(II) complexes were characterized by elemental analysis, UV-Vis, IR, and (1)H-NMR spectroscopies. The structure of the N(1)-4-benzyloxysalicylidene-S-propyl thiosemicarbazone ( 2 ) was determined by X-ray single-crystal diffraction method. The total antioxidant capacities of synthesized compounds were evaluated by using cupric reducing antioxidant capacity (CUPRAC) method. The thiosemicarbazones exhibited more potent antioxidant capacity than Ni(II) complexes. Trolox equivalent antioxidant capacity (TEAC) of 1c was found highest in tested nickel(II) complexes. In addition, antioxidant activities of tested compounds were evaluated by using the hydroxyl radical, DPPH radical, and ABTS radical scavenging abilities of these compounds.